Strong Coupling between Biomineral Morphology and Sr/Ca of Arctica islandica (Bivalvia)—Implications for Shell Sr/Ca-Based Temperature Estimates - Cornélia Brosset; Nils Höche; Kotaro Shirai; Kozue Nishida; Regina Mertz-Kraus; Bernd R. Schöne (Minerals, 2022)
Bivalve shells serve as powerful high-resolution paleoclimate archives. However, the number of reliable temperature proxies is limited. It has remained particularly difficult to extract temperature signals from shell Sr/Ca, although Sr is routinely employed in other biogenic aragonites. In bivalves, Sr/Ca is linked to the prevailing microstructure and is sometimes affected by kinetics. Here, the hypothesis is tested that temperature can be reconstructed from shell Sr/Ca once microstructure and/or growth-rate-related bias has been mathematically eliminated. Therefore, the relationship between Sr/Ca and increment width, as well as biomineral unit size, has been studied in three different shell portions of field-grown Arctica islandica specimens. Subsequently, microstructure and/or growth-rate-related variation was removed from Sr/Ca data and residuals compared to temperature. As demonstrated, the hypothesis could not be verified. Even after detrending, Sr/Ca remained positively correlated to water temperature, which contradicts thermodynamic expectations and findings from inorganic aragonite. Any temperature signal potentially recorded by shell Sr/Ca is overprinted by other environmental forcings. Unless these variables are identified, it will remain impossible to infer temperature from Sr/Ca. Given the coupling with the biomineral unit size, a detailed characterization of the microstructure should remain an integral part of subsequent attempts to reconstruct temperature from Sr/Ca.